CONSTRUCTIVISM AND TEACHING DESIGN: In Search of An Appropriate Learning Process of Sharia Entrepreneurship For Pesantren-Based University - Muslimin, JM; Reksiana, Reksiana; Munawar, Wildan (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2022)
Abstract: The development and ever-changing curriculum of university offers some possibilities for socio-educational innovation of the high-level education. It includes Pesantren-based University. Constructivist learning process may further develop such an innovation. It is designed as a flexible curriculum and multi-interpretable model of implementation and adjustable contents of learning with high focus to the practice and disseminating of knowledge. Surely, it may pave the way for designing and creating socio-educational engineering, such as building strong character and high focus to the disseminating and practice of sharia entrepreneurship. This study aims to designing constructive model of learning to disseminate and create a strong bones and practical type of sharia entrepreneurship in the milieu of Islamic boarding school (Pesantren) as it is reflected in the Pesantren Darunnajah. The research method is done through evaluative instrumental method of curriculum accompanied by critical review of learning process theories. It is done based on library research, qualitative approach as well as constructive model. It offers agenda setting of socio-educational reference and applicative model. It deserves to produce and contribute an authentic result, while such a constructive framework of educational inquiry is still rare and in the process of becoming. The result be it is proven that constructive learning process can be an alternative for developing concept as well as practical model for Pesantren-based University.Keywords: Constructivism, Design Model, Pesantren-based University, Sharia Entrepreneurship.